BEHAVIORAL EVIDENCE OF PUBLIC AIRCRAFT WITH HISTORICAL DATA: THE CASE OF BOEING 737 MAX 8 PK-LQP - Passarella, Rossi; Nurmaini, Siti (Journal of Applied Engineering Science, 2022)
This paper studies a significant amount of residual evidence characterized by the historical flight trajectory of PK-LQP (B737 MAX 8), which underwent an accident. Subsequently, this method is employed to generate novel safety-relevant knowledge based on existing flight data. At the beginning of this study, the method is applied by developing the hypothesis with the support of all data collected from online and offline reports, ADS-B data from flightradar24, and a statistical approach. This preliminary study employs Python as an essential program for the purpose of data collation and analysis. The results show that in the data offered by KNKT (The Indonesian National Transportation Safety Committee-Indonesia), the aircraft (PK-LQP) demonstrated unusual behaviour in comparison with the typical climbing phase that is produced by the dataset valid B737 MAX 8 (the ground truth data). The results also confirmed the hypothesis proposed in this study.